Anīs Chouchène’s Worldview on Women’s Rights In The Poem “Yā Imraʾata Mustaʿbadah” (A Genetic Structuralism Analysis) - Afifah, Nur; Muhammad Reko (Faculty of Ushuluddin, Adab, and Humanities Universitas Islam Negeri Salatiga, 2025)
This research focuses on men’s view of women by examining social facts, collective subjects, and global perspectives to understand author’s views in the poem Yā Imra’ata Musta‘badah (“O Enslaved Woman”). This study employs a descriptive qualitative approach using dialectical methods. Dialectics works on the concepts of “whole–part” and “understanding–explanation.” The methods used in this research were observation and note-taking, using the genetic structuralism theory by Lucien Goldmann. The results of this study reveal the presence of social facts, collective subjects, and the author’s worldview. The social facts in Yā Imra’ata Musta‘badah are represented through depictions of violence against women. The collective subject of the poem reflects disappointment with the patriarchal system in Tunisian society, leaving women vulnerable to physical and verbal abuse. In addition, the author’s worldview, Anīs Chouchène, conveys the existence of revolutionaries as forms of transformation and resistance against the violence that occured. The underlying fact driving the poem’s creation was the patriarchal society in Tunisia, where men’s interests still took precedence over women’s. Hence, women were often denied the rights and justice they deserved.